IMPLEMENTASI MATEMATIKA DALAM PENGEMBANGAN TEKNOLOGI ARTIFICIAL INTELLIGENCE - Siti Fatimah Sihotang; Metrilitna br Sembiring; Ratna Wahyuni (Universitas Islam Sumatera Utara, 2026)
This research aims to identify and map available evidence regarding the role of mathematics (such as linear algebra, discrete mathematics, computational modeling) in supporting the development of Artificial Intelligence. Mathematics is a key foundation for the development and understanding of computer science, and is a universal language used for analyzing, designing, and optimizing various aspects. Discrete mathematics, on the other hand, plays a crucial role in the foundation of artificial intelligence, particularly in the field of Artificial Intelligence. Its principles underlie many algorithms and processes that Artificial Intelligence systems rely on. Furthermore, many other mathematical concepts and principles are also used in computer science, such as propositional logic, Boolean algebra, graph theory, number theory, statistics, and algorithm analysis. Thus, computer science and mathematics are clearly closely related and complement each other. Research findings, including identifying and mapping available evidence, demonstrate that mathematics is not merely a tool, but rather the backbone of all modern Artificial Intelligence technology developments currently in use.